Herbert Hoover's support for the Zionist movement and his adoption of the project to settle Palestinian Arabs in Iraq until 1948 - Ahmed, Majed (Al-Adab Journal, 2025)
The research examines the role played by the thirty-first American President Herbert Hoover (1929-1933) in supporting the Zionist movement, both during the period before and during his assumption of the presidency of the country and after it, especially during the forties of the twentieth century through his adoption of the plan of the Zionist leader Ben Hourin  to deport the Arabs of Palestine to Iraq, which was known as the “Hoover Project.” The researcher divided his research into five axes, the first of which studied Hoover’s religious belief and its connection to his positions on the Jews and the Zionist movement. The second axis included his support for the Jews and the Zionist movement until 1928 and the role the latter played in his victory in the presidential elections. The third axis touched on Hoover’s support for the Zionist movement during the years of his presidency For the country from 1929 to 1933, which coincided with the escalation of the intensity of the Arab-Zionist conflict on the land of Palestine, and the fourth axis dealt with his plan to settle European Jews in Africa in 1943, especially with the genocide they were subjected to, while the fifth and final axis shed light on his project to deport the Arabs of Palestine to Iraq and its cooperation with supporters of corrective Zionism to implement it on the ground. However, this project did not see the light of day due to the international balances existing at that time and the beginning of the Cold War between the capitalist and socialist poles, in addition to its conflict with the American administration’s desire for its oil companies to have favor and acceptance in the Middle East region.